MODERN METHODS FOR DEVELOPING AESTHETIC AND CREATIVE THINKING IN FINE ARTS EDUCATION - Sayfiyeva Ozoda Madamin qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article analyzes contemporary methods for developing students’ aesthetic and creative thinking in fine arts education. It examines effective strategies to enhance students’ visual thinking, artistic perception, and interest in art through interactive lessons, project-based activities, and digital tools. Additionally, the study highlights the significance of student-centered approaches and a creative learning environment in fostering aesthetic thinking and artistic awareness.